Drainage devices in refractory glaucoma surgery - S. I. Anisimov; S. Yu. Anisimova; L. L. Arutyunyan; A. P. Voznyuk (Российский офтальмологический журнал)
Glaucoma is a socially sensitive disease, being one of the leading causes of irreversible visual impairment and blindness. Refractory glaucoma is one of the most severe forms of the disease as it is resistant to conservative and surgical methods of treatment. Because of pronounced postoperative fibroblastic activity of eye tissues, leading to gross scarring and obliteration of outflow paths, modern materials and methods of drainage surgery are needed. The review presents a variety of drains used today and considers in detail their main characteristics and the biocompatibility of the material used with eye tissues. Various groups of implants are presented, whose effectiveness and safety are compared and assessed. The statistics of postoperative complications and long-term results of surgical treatment are given.